2015
DOI: 10.1038/ncomms9219
|View full text |Cite|
|
Sign up to set email alerts
|

TET2 repression by androgen hormone regulates global hydroxymethylation status and prostate cancer progression

Abstract: Modulation of epigenetic patterns has promising efficacy for treating cancer. 5-Hydroxymethylated cytosine (5-hmC) is an epigenetic mark potentially important in cancer. Here we report that 5-hmC is an epigenetic hallmark of prostate cancer (PCa) progression. A member of the ten-eleven translocation (TET) proteins, which catalyse the oxidation of methylated cytosine (5-mC) to 5-hmC, TET2, is repressed by androgens in PCa. Androgen receptor (AR)-mediated induction of the miR-29 family, which targets TET2, are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 56 publications
7
85
0
Order By: Relevance
“…We confirmed the effect of TET2 KD using a second independent siRNA (siTET2-4) recently described by Takayama et al 37 (Figure 1a; Supplementary Table S3). We performed three independent treatments of LNCaP cells with siTET2-4 or a GC-matched scrambled siRNA control (scRNA) in the absence and presence of DHT.…”
Section: Resultssupporting
confidence: 89%
“…We confirmed the effect of TET2 KD using a second independent siRNA (siTET2-4) recently described by Takayama et al 37 (Figure 1a; Supplementary Table S3). We performed three independent treatments of LNCaP cells with siTET2-4 or a GC-matched scrambled siRNA control (scRNA) in the absence and presence of DHT.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, we chose this lncRNA for further study. Our ChIP-seq data (26,27) revealed ARBS in the promoter region (Chr12: 93,963,629 -93,965,465 (hg19), Ï©1.5 kbp-291 bp from the transcriptional start site (TSS) of NR_038263). Interestingly, although its expression was repressed after 48 h of androgen treatment in LNCaP cells, it was further induced even after 72 h of androgen stimulation in LTAD cells (Fig.…”
Section: Identification Of Androgen-induced Lncrnas By Directionalmentioning
confidence: 99%
“…Importantly, I have demonstrated that miR-29 family and miR-22 are highly induced by androgen in hormone-therapy resistant prostate cancer [25]. In prostate cancer clinical samples the expression level of miR-29a/b is negatively associated with that of its target gene, TET2.…”
Section: Prostate Aging and Cancer Progression Is Prominent In Aged Mmentioning
confidence: 99%
“…(B) Androgen-induced miRNA mediated TET2 repression inhibits 5-hmC modifications in FOXA1 occupied enhancer regions. By removal of 5-hmC, FOXA1 is activated and induce FOXA1 or AR-regulated genes [25]. (C) The role of enhancer RNA (eRNA) or other AR interacting lncRNA.…”
Section: The Androgen Receptor (Ar) Functions As a Nuclear Receptor Tmentioning
confidence: 99%